Glycans on death receptors as sweet markers and signaling checkpoints - Kamil Seyrek; Johannes Espe; Corinna König; Fabian Wohlfromm; Inna N. Lavrik (Frontiers in Cell Death)
Apoptosis is a form of programmed cell death that eliminates excessive and damaged cells. It can be conducted by two ways: the extrinsic and the intrinsic (mitochondrial) pathways. The extrinsic death pathway is triggered by activation of the death receptors (DRs), while the intrinsic pathway is initiated by changes at the mitochondria. The induction of life and death signals via DRs requires an intricate regulation of signal transduction. In this regard, an optimal conformation of the extracellular domain of DR is required for the Death Ligand (DL) binding and initiation of DR signaling. Glycosylation, the enzymatic attachment of carbohydrates to proteins, can influence DR conformation and thereby receptor-ligand interaction. Due to the tremendous structural diversity of glycans attached to DRs, little is known about the role of specific glycosylation subtypes influencing functions of DRs. Deciphering the role of specific glycan signatures, so-called “glyco-code”, on DRs is important to understand how glycans are involved in signal transduction. Although apoptosis has been shown to be associated with altered glycosylation patterns of glycoproteins, our understanding how glycosylation modulates apoptosis is still limited. This review focuses on summarizing our current knowledge on the modulation of cell signaling via glycosylation of DRs.